A Rare Primary Mucocutaneous Presentation of Chronic Disseminated Histoplasmosis in an Immunocompetent Young Female: A Case Report - Shende, Ankita Shashikant; Chaturvedi, Madhu Ishwarchand (Annals of Pathology and Laboratory Medicine, 2023)
Classical Histoplasmosis also known as Darling’s disease is a systemic mycosis caused by dimorphic fungus, Histoplasma capsulatum var capsulatum and Histoplasma capsulatum var duboisii. It is an opportunistic fungal infection that usually affects immunocompromised patients. Though microbiology culture methods are the gold standard, scrape cytology and histopathology give a relatively rapid diagnosis. It may pose a diagnostic dilemma on histopathology and morphology needs to be carefully studied to rule out other differentials. We present a rare case of chronic disseminated histoplasmosis with primary mucocutaneous lesions in an immunocompetent young female patient. This study is ethically approved from the institute and due written consent for publication from the patient has been taken.